Increasing leaf sizes of the vine Epipremnum aureum (Araceae): photosynthesis and respiration - Carolina Brito; Dulce Mantuano; Karen L.G. De Toni; André Mantovani (PeerJ)
The canopy leaves of allomorphic aroid vines can exceed 2,000 cm2, up to 30 times larger than respective understorey leaves. In the literature, this allomorphic increase in leaf area of aroid vines was hypothesized to improve its light foraging capacity. The viability of these large leaves depends on carbon acquisition obtained from their larger area and on the respective costs of production, maintenance and support. To evaluate and understand how leaf enlargement affects performance, we analyzed the photosynthesis and respiration of Epipremnum aureum leaves of different sizes via photosynthetic response light curves, morpho-physiology and anatomical parameters. Leaf size was increased by varying growth direction (horizontal vs. vertical) and light conditions (low vs. high). Vertical plants in high light produced leaves 9–13 times larger than those under other conditions. Saturated photosynthetic rates per area were similar across leaves of E. aureum, regardless of size, but respiration rates increased while specific leaf area decreased in larger leaves. This may suggests that larger leaves do not offset their costs per unit area in the short term, despite field observations of continuous enlargement with increased plant size. However, the high light levels able to saturate photosynthesis under field conditions are achieved only by larger leaves of E. aureum positioned at canopies (PPFD around 1,000 µmol m−2 s−1), not occurring at understory where smaller leaves are positioned (PPFD around 100 µmol m−2 s−1). This is confirmed by the higher values of the relative growth rate (RGR) and net assimilation rate (NAR) parameters exhibited by the vertical plants in high light. The saturated photosynthetic rates found here under experimental conditions for the smaller leaves of E. aureum could be related to their high invasive capacities as alien species around the world. We propose that the costs of larger aroid leaves might be outweighed by a strategy that optimizes size, morphophysiology, anatomy, photosynthesis and, lifespan to maximize lifetime carbon gain in tropical forests.